Radio-induced breast angiosarcoma: features of diagnostics and treatment (a clinical case and literature review) - I. V. Kolyadina; V. V. Kometova; Yu. V. Bikeev; S. V. Khokhlova; V. V. Rodionov (ABV-press, 2020)
Breast angiosarcoma (BAS) is an extremely rare and poorly studied neoplasm, the etiology of primary BAS remains controversial, and secondary BAS is most often radio-induced. Radio-induced breast tumors usually appear 10-20 years after the initial treatment; however, for BAS this period is much shorter and is about 4-7 years. This review presents literature data on the features of the clinic, diagnosis and treatment of BAS, as well as own clinical case observation of radio-induced sarcoma of the left breast, that developed 4 years after the primary breast cancer treatment.